Woody Species Composition, Structure, and Carbon Stock of Coffee-Based Agroforestry System along an Elevation Gradient in the Moist Mid-Highlands of Southern Ethiopia - Fikrey Tesfay; Yitebitu Moges; Zebene Asfaw (International Journal of Forestry Research)
There is a limited effort in Ethiopia to study scientifically the ecological features of traditional coffee-based agroforestry systems. This study was initiated to determine the structure, composition, and carbon stock of woody species along an elevation gradient of a traditional coffee-based agroforestry system in Yirgacheffe district, southern Ethiopia. Woody plants’ inventory was conducted in thirty-eight sampling quadrats (20 ∗ 20 m) along five elevation contours and eight transects. Thirty-eight soil samples were taken from randomly selected subplots at 0–30 cm soil depths. In this study 32, woody plant species representing 23 families were recorded. Species richness ranged from 13–17 along the elevation gradient. Woody plant diversity indices appear to have a slight variation with increasing elevation gradient. Shade tree and coffee shrub density, DBH, and height showed significant variations along the elevation gradient. Total aboveground woody biomass carbon stock along elevation gradient ranged from 11.07 to 27.48 Mg·ha−1. Soil organic carbon stock was slightly different across elevation gradients with a mean range of 83.91 to 89.29 Mg·ha−1. These indicate that the agroforestry system has significant potential of storing and enhancing ecosystem carbon stocks across all the elevation gradients. The findings generally show that agroforestry systems in the study area are diverse, structurally complex with significant carbon storage in the soil and woody biomass.